Should we screen Eastern Mediterranean COVID-19 patients for inherited thrombophilia?. (July 2021) - El Hasbani, Georges; Taher, Ali T.
Abstract: The inflammatory component of Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) creates a pro-thrombotic state that necessitates a thrombophylactic strategy for hospitalized patients. Such strategies are difficult to be standardized because certain individuals can have pro-thrombotic conditions, such as inherited thrombophilia, which pre-dispose them to an additional coagulative risk. Whether outside the hospital or when admitted, patients with inherited thrombophilia need special anticoagulant and antiplatelet attention. Identifying such patients, especially in susceptible populations like the eastern Mediterranean (EM) region, will aid primary providers in risk stratification for choosing the optimal anticoagulation or antiplatelet plan.